Materiovigilance: An Emerging Area for Exploration in Pharmaceutical Education-A Comparative Appraisal of Knowledge, Attitudes and Practices among Pharmacists and Healthcare Professionals - Komban, Shareefa; Dilip, Chandrasekhar; Vivekanandan, Kalaiselvan; Hasbiya, Kottilavalappil; Manazhy, Karthika; Sreekumar, Shyama (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Materiovigilance is essential for monitoring the safety and performance of medical devices. This study aimed to assess the Knowledge, Attitudes and self-reported Practices (KAP) of healthcare professionals regarding the use and monitoring of implantable and other medical devices in and around Perinthalmanna, Kerala, India. Materials and Methods This prospective observational study was conducted over a three-month period at KIMS Al-Shifa Super Specialty Hospital, Perinthalmanna. Healthcare professionals, including physicians, pharmacists, academicians, biomedical engineers, dentists, nurses, optometrists and students, were randomly selected to participate. Data were collected using a structured questionnaire that was validated through expert consultations and a pilot study. Quantitative data were analysed using descriptive statistics, Pearson correlation and the Likelihood ratio test, with qualitative responses undergoing thematic analysis. Results Out of 700 distributed questionnaires, 600 complete responses were obtained (86% response rate). Nurses and students comprised the majority of respondents. Knowledge of materiovigilance was moderate, with 48% demonstrating satisfactory knowledge, 45.7% unsatisfactory and 6.3% poor knowledge. While attitudes were overwhelmingly positive (92.3% satisfactory), practices were less so, with only 26.8% satisfactory and 58.8% unsatisfactory. Knowledge was significantly associated with profession and years of experience (p<0.05). Practices were also associated with these factors, but attitudes were not. Conclusion The study reveals that while healthcare professionals generally have a positive attitude towards materiovigilance, there is a significant gap in knowledge and practices. This indicates a need for enhanced training and educational programs to improve the effectiveness of materiovigilance in healthcare settings. Expanding awareness and incorporating materiovigilance into professional curricula could foster better reporting practices and enhance patient safety.
Keywords: Materiovigilance; Healthcare Professionals; Knowledge; Attitude; Practices; Medical Device Adverse Event.